Antioxidant activity of Origanum vulgare extract gel. Is it important for oral health?. Preliminary study - Galvez-Calla, Luis (2021)
Objective: To determine the antioxidant activity of the hydroalcoholic extract of Origanum vulgare through DPPH, ABTS and FRAP essays. Material and Methods: The sample collected from Origanum vulgare was dried, reduced in size and placed to macerate 500 grams of dry sample in 1000 mL of 97% ethanol for one week. After time, the macerate was processed through a filter and concentrated in an oven. The formulations were carried out and the dilutions were analyzed with the antioxidant essays. Results: DPPH Method, the 25% gel showed an IC50 of 98.485 mg / mL equivalent to the dilution of 78.789% and for the Trolox® standard, it presented IC50 of 2.48 µg / mL. ABTS Method, the 25% gel formulation presented IC50 of 3.687 mg / mL equivalent to a dilution of 77.75% and for the Trolox® standard it presented IC50 of 2.99 µg / mL, a difference from the other formulations. The results evidenced a relation between the percentage of inhibition and concentration of the samples with an accepted correlation (R2) for the gels at 25%, 50%, 75% of extract of Origanum vulgare and Trolox® of 0.9972; 0.9987 and 0.9986 respectively. FRAP Method, with fast action during the 4 minutes, being 125 mg of extract contained in the gel 25% equivalent to 4mg of Trolox®. Conclusions: It was determined that the antioxidant activity equivalent to Trolox®, with antioxidant assays, with the best average free radical uptake power (Trolox / mg) of extract was present in the gel of Extract of Origanum vulgare 25%.